(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
This article analyzes the international experience of regulating corporate relations and resolving corporate disputes, which constitute fundamental legal institutions of a modern market economy. The study provides a comprehensive comparative analysis of corporate governance models, legislative frameworks, and judicial practices across developed nations, including the USA (specifically Delaware corporate law and the Business Judgment Rule), the UK, Germany, France, Japan, and Singapore, all anchored in the OECD’s Corporate Governance Principles. Special attention is given to the pivotal role of specialized corporate courts—such as the Delaware Court of Chancery and the Singapore International Commercial Court—as well as alternative dispute resolution (ADR) mechanisms like mediation and arbitration. Furthermore, the text addresses contemporary legal trends, including the integration of digital technologies and ESG (Environmental, Social, and Governance) standards. Ultimately, the article outlines actionable paths for integrating these global best practices into the legal system of Uzbekistan to improve the local investment climate, elevate corporate governance quality, and minimize corporate disputes.